Relationship between farmer’s characteristic and Watermelon (Citrullus vulgaris) in the Sugih Waras village Muara Sugihan District Banyuasin Regency - Prilierdi, Ayogi; Abubakar, Rafeah; Iskandar, Sutarmo (Universitas Muhammadiyah Palembang, 2015)
The purpose of this study was to determine the development of watermelon farming, to determine the relationship of the characteristics of watermelon farmers to farm income.This research was conducted in the Sugih Waras Village Muara Sugihan District Banyuasin Regency of March until the month of May 2015. The method used was a survey, the data collected is of primary data and secondary data that has to do with the problems and objectives of this study. While the sampling method used is the method by farmers census respondents as many as 16 people. tabulation processing, while for calculating income calculation preceded reception and production costs, then using Spearman rank correlation to determine the relationship characteristics of watermelon farmers and farm income.The survey results revealed that within three (3) years of the last developments of watermelon farm in the Sugih Waras village Muara Sugihan District Banyuasin Regency always increased and relationships farmer characteristics (age, education and experience of farming) shows the positif relationship and income.